Fiscal policy instruments for inclusive labour markets: A review - Ekkehard Ernst; Rossana Merola; Jelena Reljic (Global Labor Organization (GLO), 2024)
This study provides a critical assessment of various fiscal policy instruments - including direct public job creation, active labour market and care policies, social protection measures and tax reforms - and their effectiveness in supporting the most vulnerable groups in the labour market. Although much of the literature has focused on the quantitative effects of fiscal policy, this article concentrates on the qualitative aspects and examines the role of fiscal instruments in achieving a more inclusive and fair labour market. Our review shows that the empirical literature tends to overemphasise the capacity of individual policies to mitigate inequalities, neglecting the complex interdependencies among various mechanisms and policies in place. We argue, instead, that a systematic approach is necessary to ensure equitable access to good jobs and to address the disparities between different labour market groups. We also identify significant research gaps, such as the need for longitudinal studies on the long-term policy impacts, an exploration of the regional disparities within the policy-inequality nexus and the sector-specific effects of fiscal measures, especially relevant in the context of the green and digital transition.
Keywords: E6; H2; H3; H5; J1; J2; 330; fiscal policy; policy coordination; policy implementation; labour market outcomes; inclusive labour markets; social protection